Influence of feed additives and feed processing techniques on monogastric nutrition - Braun, Michaela Briane (Kansas State University, 2020)
A total of 5 experiments were conducted to evaluate the influence of feed additives and processing techniques on monogastric nutrition. First, 2 experiments were conducted to assess how multicarbohydrase inclusions affected the digestibility and growth performance of broiler chickens. A 150 kcal/kg and 151 kcal/kg increase in AME and AMEn, respectively, were observed with the inclusion of the proprietary enzyme blend 1 when compared to the control diet. Additional enzyme blends were tested in experiment 2, and no evidence of a growth response was observed. The second objective pertained to determining the optimal conditioning temperature and die specifications when pelleting diets for nursery pigs. Treatments consisted of a mash control (MC) and 6 pelleted treatments manufactured using 2 different pellet dies (length/diameter [L:D]: 6.7 and 2.7) and 3 different conditioning temperatures (low, medium, high). Overall, pelleted diets showed poorer ADG (P = 0.049), decreased ADFI (P = 0.001) and improved G:F (P = 0.020) and no differences in final BW compared to the MC. There was also a decrease in pellet quality when treatments were manufactured on the 2.7 L:D die; however, these differences did not result in a growth performance response due to conditioning temperature or die. In conclusion, pelleting diets improves G:F but care should be taken when pelleting at high conditioning temperature when considering available lysine. The third objective evaluated how changing variables when grinding corn influences subsequent corn particle size and flow ability. Experiment 1 determined the effects of whole corn moisture and hammermill screen size on subsequent ground corn particle size and flowability. As received (14.5% moisture) corn resulted in decreased (P < 0.029) particle size and an increased standard deviation compared to the high moisture (16.7% moisture) corn. Increased moisture content of corn increased (P < 0.038) composite flow index and tended to decrease (P < 0.055) angle of repose and critical orifice diameter (P = 0.056). Decreasing hammermill screen size increased moisture loss by 0.55%, corn particle size by 126 µm, and resulted in poorer flowability as measured by percent compressibility and angle of repose. High moisture corn increased subsequent particle size by 89 µm, therefore improving flowability as measured by CFI. For experiment 2, the effect of hammermill tip speed, assistive air flow rate and screen hole diameter on hammermill throughput and characteristics of the ground corn material was determined. Treatments were arranged in a 3 × 3 × 3 factorial design with 3 tip speeds (755, 995, 1,235 m/s), 3 screen hole diameters (2.3, 3.9, 6.3 mm) and 3 air assist system settings (60, 80, and 100% of fan motor load). Increasing screen hole diameter linearly increased (P = 0.001) corn particle size whereas increasing hammer tip speed linearly decreased (P = 0.001) particle size. The main effect of assistive air flow did not significantly impact corn particle size. In conclusion, adjusting hammer tip speed is a viable method of reducing particle size. With increased hammer tip speed come flowability concerns but these can be lessened with increased air assist.
Keywords: Monogastric nutrition; Grinding; Flowability; Corn; Hammermill; Pelleting